Mechanosensitivity of Murine Lung Slowly Adapting Receptors: Minimal Impact of Chemosensory, Serotonergic, and Purinergic Signaling - Domnik, Nicolle J.; Vincent, Sandra G.; Fisher, John T. (Frontiers in Physiology, 2022)
Murine slowly adapting receptors (SARs) within airway smooth muscle provide volume-related feedback; however, their mechanosensitivity and morphology are incompletely characterized. We explored two aspects of SAR physiology: their inherent static mechanosensitivity and a potential link to pulmonary neuroepithelial bodies (NEBs). SAR mechanosensitivity displays a rate sensitivity linked to speed of inflation; however, to what extent static SAR mechanosensitivity is tuned for the very rapid breathing frequency (Bf) of small mammals (e.g. mouse) is unclear. NEB-associated, morphologically-described smooth muscle-associated receptors (SMARs) may be a structural analogue for functionally-characterized SARs, suggesting functional linkages between SARs and NEBs. We addressed the hypotheses that: 1) rapid murine Bf is associated with enhanced in vivo SAR static sensitivity; 2) if SARs and NEBs are functionally linked, stimuli reported to impact NEB function would alter SAR mechanosensitivity. We measured SAR action potential discharge frequency (AP f, action potentials/s) during quasi-static inflation (0-20 cmH2O trans-respiratory pressure (PTR)) in NEB-relevant conditions of hypoxia (FIO2=0.1), hypercarbia (FICO2=0.1), and pharmacologic intervention (serotonergic 5-HT3 receptor antagonist, Tropisetron, 4.5mg/kg; P2 purinergic receptor antagonist, Suramin, 50 mg/kg). In all protocols we obtained: 1) AP f vs PTR; 2) PTR threshold; and 3) AP f onset at PTR threshold. The murine AP f vs PTR response comprises high AP f (average maximum AP f: 236.1±11.1 AP/s at 20 cmH2O), a low PTR threshold (mean 2.0±0.1 cmH2O) and a plateau in AP f between 15-20 cmH2O. Murine SAR mechanosensitivity (AP f vs PTR) is up to 60% greater than that reported for larger mammals. Even the maximum difference between intervention and control conditions was minimally impacted by NEB-related alterations: Tropisetron -7.6±1.8% (p=0.005); Suramin -10.6±1.5% (p=0.01); hypoxia +9.3±1.9% (p<0.001); hypercarbia -6.2±0.9% (p<0.001). We conclude that the high sensitivity of murine SARs to inflation provides enhanced resolution of operating lung volume, which is aligned with the rapid Bf of the mouse. We found minimal evidence supporting a functional link between SARs and NEBs and speculate that the <10% change in SAR mechanosensitivity during altered NEB-related stimuli is not consistent with a meaningful physiologic role.